2006
DOI: 10.1111/j.1532-5415.2006.00742.x
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Blood Pressure and Survival over 9 Years in a General Population Aged 85 and Older

Abstract: Low systolic BP may be partially related to poor general health and poor vitality, but the very old may represent a select group of individuals, and the use of BP-lowering medications needs to be evaluated in this group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
95
1
8

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(109 citation statements)
references
References 37 publications
5
95
1
8
Order By: Relevance
“…Some indicate linearly worse outcomes with higher BP (4), whereas others suggest that BP has a J-shaped association with outcomes (5)(6)(7)(8) and that high BP has a diminished or reversed association with adverse outcomes in elderly patients. Clinical trials offer some indication that treating elevated BP to moderately low levels may decrease cardiovascular events in very old individuals (9,10), but it remains unclear whether using even stricter targets is beneficial (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Some indicate linearly worse outcomes with higher BP (4), whereas others suggest that BP has a J-shaped association with outcomes (5)(6)(7)(8) and that high BP has a diminished or reversed association with adverse outcomes in elderly patients. Clinical trials offer some indication that treating elevated BP to moderately low levels may decrease cardiovascular events in very old individuals (9,10), but it remains unclear whether using even stricter targets is beneficial (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] Taking into account that some epidemiological studies have suggested that BP is inversely related to the risk of death in patients 80 years or older, there is very scarce information about the best practices in the elderly population. 4,19,20 However, recent clinical trials such as HYVET 12 provide consistent evidence that antihypertensive treatment in persons 80 years of age or older is beneficial. In this context, surveys such as PRESCAP 2006 are important because they depict clinical practice and provide an accurate picture of the hypertensive population 80 years of age or older who are managed in primary care.…”
Section: Discussionmentioning
confidence: 99%
“…Although the prevalence of hypertension increases with age (about three-quarters of patients 80 years or older are hypertensives), the available evidence about the benefits of treating hypertension in that patient population is scarce. 4,5 Most randomized controlled trials involving older adults either have excluded those 80 years or older or have included too few participants. [6][7][8][9] Systolic blood pressure (BP) increases with age, whereas diastolic pressure rises until the 50 s and falls after that.…”
Section: Introductionmentioning
confidence: 99%
“…Аналогичные результаты были получены и в ряде об-сервационных исследований [25][26][27]. В частности, в ис-…”
Section: эффективность антигипертензивной терапии у пациентов старше unclassified